Production of polyhydroxyalkanoates by native halophilic bacteria using Solanum tuberosum L. shell starch - Guzmán, César (2017)
The aim of this study was to determine the concentration of starch Solanum tuberosum L. “potato” peels for the production of polyhydroxyalkanoates, PHA, from native halophilic bacteria as an alternative to reduce production costs of these biopolymers, possible replacements for petrochemical plastics. The bacteria were isolated of water samples of eight saline Lambayeque region and were enriched in HM1 broth at 30 °C with 5, 10, 15, 20, 25 and 30 g 100 mL-1 NaCl. Dilutions were performed subsequently, aliquots were taken and plated on HM1 agar, 203 isolates of halophilic bacteria were obtained, they were grown in HM2 broth with 10 g.L-1 glucose as carbon source and the 38.92% of the isolates showed PHA granules stained by Sudan Black B. Twenty bacteria with PHA granules in 65 – 75% over carried to fermentation, reaching between 0.174 to 0.889 g.g-1 of yield Y (p / x). Three isolates were selected with the highest values among which Halomonas sp M4C1 grew and synthesized PHA in HM2 broth with 5, 10, 15 and 20 g.L-1 of starch as carbon source, reaching 0.019; 0.016; 0.007 y 0.006 g.L-1 of PHA, with 0.177; 0.111; 0.056 and 0.066 g.L-1 of biomass after 20, 40, 24 and 16 hours respectively. The highest yield of 0.144 g.g-1 corresponded to 10 g.L-1 of starch demonstrating that this concentration is feasible PHA production by native halophilic bacteria.